HOW CULTURAL VALUES CONTRIBUTE TO STUDENT PERFORMANCE IN THE SCHOOL CONTEXT: A CASE OF NJOMBE REGION, TANZANIA - Bernadetha Haule, Daigo; Shaker, Thanaa; Haule Lyengeru, Jackob (IAIN Surakarta, 2024)
This study examines the relationship between cultural values and student performance in the school setting. It addresses how cultural values shape students’ academic achievements and overall educational success. While previous research has explored the role of cultural values in education, there has been limited analysis of their direct effect on student performance in specific contexts, such as Njombe. This research implemented behaviourism theory and adopted a mixed- method case study approach. Data were collected using questionnaires and interviews with 42 individuals, including students, teachers, and educational administrators from public or governmental schools in the Njombe region, southern Tanzania. The findings indicate that cultural values substantially impact student's academic success, with most participants acknowledging this influence. However, perceptions vary, revealing challenges and opportunities in integrating cultural factors into education. The insights provided by this study underscore the importance of incorporating cultural considerations into educational practices and interventions to enhance student achievement.